Competency and Certification's Impact on Work Productivity: Motivation as an Intervening Variable - Reniati (FEB - Universitas Lampung, 2025)
This study examines the influence of competency and certification on work productivity, with work motivation as a mediating variable. Focusing on Police Sector Chiefs in the Bangka Belitung Islands Regional Police, it uses a quantitative approach with SEM-PLS and bootstrapping for data analysis. Findings show that both competency and certification significantly improve productivity, with motivation strengthening this relationship. The study highlights the importance of enhancing professional capacity through training and certification, especially when supported by strong motivation. Its theoretical contribution lies in integrating competency, certification, and motivation in one model, offering a fresh perspective on police HR development. The focus on Police Sector Chiefs presents a novel context, rarely explored in previous research. However, the study is limited to a specific region and does not include other influencing factors like organizational culture. Despite this, it provides valuable insights for developing more effective and adaptive HR policies in the police force.